Russia may interfere in Danish election, exploiting chaos sown by US, spies warn - France-Presse, Agence (The Guardian, 2026)
US threats to seize Greenland have created ‘new international fault lines’ that can be used to spread disinformation, Danish intelligence agencies say
Russian Federation
Keywords: Denmark; Europe; Greenland; Russia; US news; Ukraine; World news